Online Dispute Resolution (ODR) sebagai Mekanisme Penyelesaian Sengketa E-Commerce dalam Perspektif Kepastian Hukum di Indonesia - Naufal Raka Maulana; Rayhan Nadindra Alfatih; Tutur Nurul Hidayatulloh; Ahyana Ikhwana Ramadhana; Muhammad Luthfi Al Farizi; Rafy Muhammad Fathsa; Ghiffaridz Valdzan Arrazi; Nandang Najmudin (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2026)
The e-commerce is a familiar acronym to lots of apparently active internet explorers. E-commerce has been responsible for the improvements factors of this era of which we know at the very moment as well as its disputes and the solvings following it. The concrete and true step is supposed to be taken by law, in a proper, recognized way of conduct. This research focuses mainly on studying the Online Dispute Resolutions (ODR), including its various definitions, regulations, and how entire dispute is solved at the end from this. This research uses the qualitative method with descriptive-analysis approach. With the correct perspective and proper navigations, ODR is, undoubtfully, able to regulate and organize most, if not all, the e-commerce disputes handlings. At the end of the day, ODR is the perfect method of how we could solely finish disputes with proper, efficient, yet uniquely imperfect method of non-litigation way of any case related to breach of contract. Through ODR, parties are able to fairly balance their needs to operate and function to handle their any case thoroughly thus it has been proven, by this research, to be a fair legal way to solve disputes involving any person.